Roles of Rho-associated kinase in lung cancer review - Zakaria, Muhammad Asyaari; Rajab, Nor Fadilah; Eng, Wee Chua; Selvarajah, Gayathri Thevi; Masre, Siti Fathiah (Spandidos Publications, 2020)
Lung cancer is one of the most lethal forms of cancer known to man, affecting millions of individuals worldwide. Despite advancements being made in lung cancer treatments, the prognosis of patients with the disease remains poor, particularly among patients with late‑stage lung cancer. The elucidation of the signaling pathways involved in lung cancer is a critical approach for the treatment of the disease. Over the past decades, accumulating evidence has revealed that Rho‑associated kinase (ROCK) is overexpressed in lung cancer and is associated with tumor growth. The present review discusses recent findings of ROCK signaling in the pathogenesis of lung cancer that were conducted in pre‑clinical studies. The significant role of ROCK in cancer cell apoptosis, proliferation, migration, invasion and angiogenesis is discussed. The present review also suggests the use of ROCK as a potential target for the development of lung cancer therapies, as ROCK inhibition can reduce multiple hallmarks of cancer, particularly by decreasing cancer cell migration, which is an initial step of metastasis.